Child and adolescent benzodiazepine exposure and overdose in the United States: 16 years of poison center data. (2nd July 2020) - Friedrich, Joseph M.; Sun, Christie; Geng, Xue; Calello, Diane P.; Gillam, Michael; Medeiros, Kaelen L.; Smith, Mark; Ruck, Bruce; Mazer-Amirshahi, Maryann
Abstract: Background: Recently, there has been an increase in prescription drug abuse and related fatalities. Although opioid analgesics are commonly implicated, there have been significant increases in the prevalence of benzodiazepine exposures and overdoses. Objective: To describe national trends in pediatric benzodiazepine exposures from 2000 to 2015. Methods: A retrospective database analysis was conducted. Data regarding benzodiazepine exposures in children ages 0 to <18 years reported to participating United States poison centers from January 2000 through December 2015 were obtained from the National Poison Data System. Population data were obtained from the US Census Bureau to determine annual population estimates. Data were analyzed using chi-square tests. Results: A total of 296, 838 pediatric benzodiazepine exposures were identified during the study period. The rate of pediatric benzodiazepine exposure increased 54% between 2000 and 2015. The severity of medical outcomes also increased, as did the prevalence of co-ingestion of multiple drugs, especially in children ages 12 to <18 years. Nearly half of all reported exposures in 2015 were documented as intentional abuse, misuse, or attempted suicide, reflecting a change from prior years. The most commonly identified pediatric benzodiazepines of exposures were alprazolam, clonazepam, and lorazepam. Conclusions: The rate and severity of reported pediatric benzodiazepine exposure is increasing over time. Adolescent exposures are of specific concern, as co-ingestion and intentional abuse were found to be more common in this group. Medical providers and caretakers should be cognizant of this growing epidemic to avoid preventable harm to adolescents, young children, and infants.